CD73-dependent generation of extracellular adenosine by vascular endothelial cells modulates de novo lipogenesis in adipose tissue - Jaeckstein, Michelle Y.; Schulze, Isabell; Zajac, Michael Wolfgang; Heine, Markus; Mann, Oliver; Pfeifer, Alexander; Heeren, Joerg (Frontiers in Immunology, 2024)
Next to white and brown adipocytes present in white and brown adipose tissue (WAT, BAT), vascular endothelial cells, tissue-resident macrophages and other immune cells have important roles in maintaining adipose tissue homeostasis but also contribute to the etiology of obesity-associated chronic inflammatory metabolic diseases. In addition to hormonal signals such as insulin and norepinephrine, extracellular adenine nucleotides modulate lipid storage, fatty acid release and thermogenic responses in adipose tissues. The complex regulation of extracellular adenine nucleotides involves a network of ectoenzymes that convert ATP via ADP and AMP to adenosine. However, in WAT and BAT the processing of extracellular adenine nucleotides and its relevance for intercellular communications are still largely unknown. Based on our observations that in adipose tissues the adenosine-generating enzyme CD73 is mainly expressed by vascular endothelial cells, we studied glucose and lipid handling, energy expenditure and adaptive thermogenesis in mice lacking endothelial CD73 housed at different ambient temperatures. Under conditions of thermogenic activation, CD73 expressed by endothelial cells is dispensable for the expression of thermogenic genes as well as energy expenditure. Notably, thermoneutral housing leading to a state of low energy expenditure and lipid accumulation in adipose tissues resulted in enhanced glucose uptake into WAT of endothelial CD73-deficient mice. This effect was associated with elevated expression levels of de novo lipogenesis genes. Mechanistic studies provide evidence that extracellular adenosine is imported into adipocytes and converted to AMP by adenosine kinase. Subsequently, activation of the AMP kinase lowers the expression of de novo lipogenesis genes, most likely via inactivation of the transcription factor carbohydrate response element binding protein (ChREBP). In conclusion, this study demonstrates that endothelial-derived extracellular adenosine generated via the ectoenzyme CD73 is a paracrine factor shaping lipid metabolism in WAT.